Shrinking cities in Poland: identification of the phenomenon and its socioeconomic implications - Wichowska, Anna (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: A steady decline in the urban population is a pressing problem for many countries in the world. Urban depopulation is also observed in Poland. This phenomenon not only leads to demographic changes, but it also has economic, financial, social, and environmental implications. Numerous studies have shown that urban shrinkage has different causes and implications, which reflects the complex and multifaceted character of the problem Aim: The aim of this article was to identify and classify shrinking cities in Poland based on the criterion of a steady decline in the urban population, to classify shrinking cities based the rate of urban depopulation, and to examine the relationship between urban depopulation and the indicators of local socioeconomic development. Results: Urban shrinkage was explored not only in the theoretical, but also in the practical context because this process can be expected to intensify in the future. The study demonstrated that the rate of urban shrinkage in Poland increased between 2012 and 2021 and affected a growing number of cities. Urban shrinkage was identified in 174 urban municipalities with the use of the proposed approach. These cities can be divided into three groups based on the rate of urban shrinkage. The identified groups of cities were characterized by different levels of economic growth and different relationships with the analyzed indicators of urban shrinkage.